Fabricating quality in education : data and governance in Europe - Ozga, Jennifer (Routledge, 2011)
How is European education governed? Data's now the lifeblood of education governance. At the international level, organisations like the OECD steer education systems through their programmes of assessment and the European Commission's project of creating the most successful knowledge economy in the world is driven by data collection, analysis and comparison. At the national level, policy-makers increasingly depend on data to show them where they are positioned, in relation to their competitors, and draw on data to justify policy directions. Within systems, schools and teachers have ...